Всемирный доклад о наркотиках, 2018 год - United Nations Office on Drugs; Crime (United Nations, 2018)
The 2018 World Drug Report will include an updated overview of recent trends on production, trafficking and consumption of key illicit drugs as well as highlighting a thematic area of concern. The Report contains a global overview of the baseline data and estimates on drug demand and supply, and it provides the reference point of information on the drug situation worldwide. The thematic focus of the 2018 Report will present information and issues related to drugs and women, youth and older people.